Bootstrap Leadership : 50 Ways to Break Out, Take Charge, and Move Up. - Arneson, Steve (BK business book., 2010)
Helps aspiring leaders overcome cutbacks in corporate training and 'pull themselves up' the leadership ladder in 50 practical, tested tips. This title is suitable for designing your own personal leadership development program. No one is going to just give you that next promotion you have to develop yourself and earn it.